Simultaneous quantification of empagliflozin, linagliptin and metformin hydrochloride in bulk and synthetic mixture by RP-LC method - Ishita M. Patel; Usmangani K. Chhalotiya; Harsha D. Jani; Devansh Kansara; Hetaben M. Kachhiya; Dimal A. Shah (SpringerOpen, 2021)
Abstract Background Extensive literature review revealed that no RP-LC method has been developed for simultaneous estimation of EMPA, LINA and MET in combined dosage form. This is a newer combination approved by USFDA on 4th June 2019 and it is launch in the United State Market on 27th January 2020. Result A simple, sensitive, specific, precise and accurate reverse phase-high performance liquid chromatography (RP- HPLC) method has been developed for simultaneous estimation of Empagliflozin, Linagliptin and Metformin HCl in bulk and synthetic mixture. Phenomenex C18 column (250 mm × 4.6 mm, 5 µm) was used as stationary phase for chromatographic separation through isocratic elution using Acetonitrile: Methanol: Water in a ratio (27: 20: 53, v/v/v) pH 4 adjusted with 1% Ortho-phosphoric acid as mobile phase at flow rate 1 ml/min. PDA detector was used for simultaneous analysis of all three drugs at common wavelength 223 nm and the each injection volume was 20 µl. The linearity range for Empagliflozin, Linagliptin and Metformin HCl was found to be 0.5-5 µg/ml, 0.25-2.5 µg/ml, and 50-500 µg/ml, respectively. The retention time for Empagliflozin, Linagliptin and Metformin HCl was found to be 14.5 min, 3.4 min and 2.01 min, respectively. The percentage (%) recovery was found to be 99.98-100.81% for Empagliflozin, 99.33-100.57% for Linagliptin and 100.65-101.35% for Metformin HCl respectively. Conclusion As per the international Conference on Harmonisation (ICH) Q2 (R1) guideline, proposed RP-LC method validation has been carried out. The proposed RP-LC method was repeatable and selective as per statistical analysis and it can be use for simultaneous estimation of Empagliflozin, Linagliptin and Metformin HCl in bulk and synthetic mixture. The proposed method might be applied for simultaneous estimation of all three drugs in pharmaceutical formulation.